Paciente de sexo femenino de 71 años de edad con edema pulmonar. - Proaño Bazán, Andrés Leonel (2020)
The present clinical case study deals with a 71-year-old patient who entered the intensive care area due to impaired consciousness, desaturation, plus hypotension. The chest x-ray shows typical images of acute lung edema, for which he required ventilatory assistance to help improve his symptoms among other medications such as loop diuretics for the progress of his pathology. The objective of this study is to describe the types of acute lung edema, as well as to analyze the predisposing risk factors, in addition to analyzing the ventilatory strategies applied in it and describing the pathophysiological clinical manifestations and their treatment guidelines. In the follow-up of this clinical case, it was obtained as a result that the patient responded favorably both to the establishment of the ventilatory strategy applied as well as to the pharmacological medical treatment.